A Monte Carlo model for mean glandular dose evaluation in spot compression mammography. Issue 7 (13th June 2017) - Sarno, Antonio; Dance, David R.; van Engen, Ruben E.; Young, Kenneth C.; Russo, Paolo; Di Lillo, Francesca; Mettivier, Giovanni; Bliznakova, Kristina; Fei, Baowei; Sechopoulos, Ioannis
Abstract : Purpose: To characterize the dependence of normalized glandular dose (DgN) on various breast model and image acquisition parameters during spot compression mammography and other partial breast irradiation conditions, and evaluate alternative previously proposed dose‐related metrics for this breast imaging modality. Methods: Using Monte Carlo simulations with both simple homogeneous breast models and patient‐specific breasts, three different dose‐related metrics for spot compression mammography were compared: the standard DgN, the normalized glandular dose to only the directly irradiated portion of the breast (DgNv), and the DgN obtained by the product of the DgN for full field irradiation and the ratio of the mid‐height area of the irradiated breast to the entire breast area (DgNM ). How these metrics vary with field‐of‐view size, spot area thickness, x‐ray energy, spot area and position, breast shape and size, and system geometry was characterized for the simple breast model and a comparison of the simple model results to those with patient‐specific breasts was also performed. Results: The DgN in spot compression mammography can vary considerably with breast area. However, the difference in breast thickness between the spot compressed area and the uncompressed area does not introduce a variation in DgN. As long as the spot compressed area is completely within the breast area and only the compressed breast portion is directly irradiated, its position and size does not introduce a variation in DgN for the homogeneous breast model. As expected, DgN is lower than DgNv for all partial breast irradiation areas, especially when considering spot compression areas within the clinically used range. DgNM underestimates DgN by 6.7% for a W/Rh spectrum at 28 kVp and for a 9 × 9 cm 2 compression paddle. Conclusion: As part of the development of a new breast dosimetry model, a task undertaken by the American Association of Physicists in Medicine and the European Federation of Organizations of Medical Physics, these results provide insight on how DgN and two alternative dose metrics behave with various image acquisition and model parameters.